Mechanical loading alleviated the inhibition of β2‐adrenergic receptor agonist terbutaline on bone regeneration. Issue 12 (5th November 2021) - Wang, Ziyan; Liu, Yang; Zhang, Jianing; Lin, Minmin; Xiao, Chufan; Bai, Haoying; Liu, Chao
Abstract: The long‐term use of adrenergic medication in treating various conditions, such as asthma, increases the chances of bone fracture. Dynamic mechanical loading at a specific time is a method for improving bone quality and promoting healing. Therefore, we hypothesized that precisely controlling the mechanical environment can contribute to the alleviation of the negative effects of chronic treatment with the common asthma drug terbutaline, which is a β2‐adrenergic receptor agonist that facilitates bone homeostasis and defect repair through its anabolic effect on osteogenic cells. Our in vitro results showed that terbutaline can directly inhibit osteogenesis by impairing osteogenic differentiation and mineralization. Chronic treatment in vivo was simulated by administering terbutaline to C57BL/6J mice for 4 weeks before bone defect surgery and mechanical loading. We utilized a stabilized tibial defect model, which allowed the application of anabolic mechanical loading. During homeostasis, chronic terbutaline treatment reduced the bone formation rate, the fracture toughness of long bones, and the concentrations of bone formation markers in the sera. During defect repair, terbutaline decreased the bone volume, type H vessel, and total blood vessel volume. Terbutaline treatment reduced the number of osteogenic cells. Periostin, which was secreted mainly by Prrx1+ osteoprogenitors and F4/80+ macrophages, was inhibited by treating the bone defect with terbutaline. Interestingly, controlled mechanical loading facilitated the recovery of bone volume and periostin expression and the number of osteogenic cells within the defect. In conclusion, mechanical loading can rescue negative effects on new bone accrual and repair induced by chronic terbutaline treatment.